2017
DOI: 10.3389/fped.2017.00288
|View full text |Cite|
|
Sign up to set email alerts
|

Sleep Characteristics of the Staff Working in a Pediatric Intensive Care Unit Based on a Survey

Abstract: The objective is to evaluate the sleep characteristics of the staff working in a pediatric intensive care unit (PICU). They were asked to complete an anonymous survey concerning the characteristics and quality of their sleep, as well as the impact of sleep disturbances on their work and social life, assessed by Functional Outcomes of Sleep Questionnaire (FOSQ)-10 questionnaire. The response rate was 84.6% (85% females): 17% were doctors, 57% nurses, 23% nursing assistants, and 3% porters. 83.8% of them worked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…A study done on 2737 interns showed that extended shifts each month increase the risk of car accidents while driving back home by 16.2% 20. Although in this study, the number of calls was not significantly associated with excessive daytime sleepiness, frequent on-call duties and poor sleep quality and quantity have been noted to have a negative impact on a person's social and personal life,10,21 and have been associated with depressive symptoms.22…”
contrasting
confidence: 59%
See 1 more Smart Citation
“…A study done on 2737 interns showed that extended shifts each month increase the risk of car accidents while driving back home by 16.2% 20. Although in this study, the number of calls was not significantly associated with excessive daytime sleepiness, frequent on-call duties and poor sleep quality and quantity have been noted to have a negative impact on a person's social and personal life,10,21 and have been associated with depressive symptoms.22…”
contrasting
confidence: 59%
“…9 Moreover, another study that evaluated the sleep quality among the staff working in a pediatric ICU found that night shift workers had poorer sleep quality compared to workers who had fixed shifts. 10 To the best of our knowledge, this is the first study in Bahrain that aimed to evaluate the sleep quality among physicians with on-call duties. Our hypothesis was that if on-call duties are for longer than 20 hours and cause sleep disturbance, then many BDF doctors will have poor sleep quality.…”
Section: Introductionmentioning
confidence: 99%
“…Even though severalstudies for the health-promoting behaviors of the nurses have been conducted in the literature (9,11,13,22,23), no study on the health-promoting behaviors of nurses working in the pediatrics clinics has been found. Also, although in the literature there are studies for the sleeping states of the nurses working at pediatric intensive care services (24,25), no study examining the correlation between the health-promoting behaviors and sleeping states of the nurses working at all the pediatric clinics has been found. Thus, the aim of this study wasto determine the relationship between health-promoting lifestyle behaviors and sleep quality of the nurses working in the pediatric clinics.…”
Section: Introductionmentioning
confidence: 99%
“…Shiftwork means employment outside the established workday, which is typically 8 am -4 pm. 1 Essential for the successful functioning of institutions requiring 24-hour operation (such as hospitals), it requires employees to work outside of physiologic sleep hours. A shift worker is defined as a person who does not work a standard daytime schedule.…”
mentioning
confidence: 99%